STRUCTURAL MODELS FOR SUSTAINABLE TOURISM DEVELOPMENT IN MEDAN CITY - Edy Sahputra Sitepu; Rismawati Rismawati; Dewi Comala; Edi Putra Berutu; Jamardua Haro; Agus Edy Rangkuti (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Medan City is currently designated as one of the 20 national tourism destinations that implement Sustainable Tourism Development (STD) in Indonesia. The commitment to implement STD nationally is marked by the signing of the text of the Memorandum of Understanding (MoU) of 20 Regional Heads who are committed to implementing STD together with the Indonesian Ministry of Tourism. Furthermore, under the supervision of the Republic of Indonesia Ministry of Tourism, 20 existing Regencies / Cities made various improvements in each region so that they were finally eligible for STD certification from the STD international certification body. Medan City itself, through the Medan City Tourism Office, related to the implementation of the STD, has established a number of leading tourism destinations. It is hoped that in the future, Medan City will have tourist destinations that have received STD certification. This research was conducted to formulate a model of implementing sustainable tourism development in Medan with a total sample of 220 people spread over 11 leading tourist destinations in the city of Medan, samples were taken with a purposive random sampling technique. The research variables used include; sustainable management, socio-cultural benefits, economic benefits for the surrounding community, environmental benefits and the application of sustainable tourism. Data analysis was carried out with a structural model of the Structural Equation Model (SEM) with the help of Amos 22 software. The results showed that the management aspects, economic aspects, socio-cultural aspects of environmental aspects, and the impact of tourism, directly and indirectly, have a positive effect on the implementation of sustainable tourism in the city of Medan.